Dynamic linkages among price indices and type of inflation in Malaysia - Murdipi, Rafiqa; Law, Siong Hook (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2014)
This study examines the dynamic linkages among consumer price, producer price, industrial production and import price indices in Malaysia using monthly data from 2005 to 2011. The empirical results based on the Johansen multivariate cointegration test reveal that there is a long-run relationship among these indices. The long-run estimations indicate that industrial production and import price are statistically significant determinants of consumer price index, which indicate the phenomenon of demand-pull and international transmission or imported inflation in the long-run. However, the higher producer price is associated with higher inflation or cost-push inflation in the short-run.